Short term memory for serial order: unraveling individual differences in the use of processes and changes across tasks - Koppenol-Gonzalez, Gabriela; Bouwmeester, Samantha; Vermunt, Jeroen K. (Frontiers in Psychology, 2013)
In this study we investigated whether we could distinguish the use of specific verbal and visual short term memory (STM) processes in children, or whether the differences in memory performance could be interpreted only in terms of quantitative differences. First, the number of processes involved in the responses on six STM tasks (serial order reconstruction) of 210 primary school children aged 5 to 12 years was examined by means of latent states. The number of items to reconstruct was manipulated to unravel quantitative differences in responses (high or low performance), and the similarity of the items was manipulated to distinguish qualitative differences in responses (verbal or visual processing). Furthermore, we examined how children changed from one type of process to another on tasks with list lengths of 3, 5, and 7 items by means of the dynamics between the latent states using a latent Markov model. The results showed that two latent states representing the use of specific verbal and visual STM processes could be distinguished on all the tasks. Moreover, two latent states showing merely differences in performance were also found. These findings underline the value of latent variable models to unravel differences between as well as within individuals in the use of cognitive processes.